Polymer Film Coatings on Metallic Electrodes Through Post-Polymerization of Acrylamide - Ji Shukla, Ram; Sinha, A.K. (Asian Journal of Chemistry, 2010)
Electro-initiated post-polymerization of acrylamide in aqueous zinc chloride system on aluminium anode and steel cathode is successfully carried out. It has been observed that the cathode is coated uniformly with poly-acrylamide during post polymerization. Appreciable polymer coatings have been obtained when the system is allowed to stand undisturbed for few hrs after electroinitiation.